Pengaruh Penggunaan Model Pembelajaran Auditory Intellectually Repetition (AIR) terhadap Musikalitas Peserta Didik di Sekolah Dasar - Euis Aminah Qodarwati, - (2022)
This research is motivated because the students' musical ability is still low because teachers only use conventional learning models. This study aims to find out how to compare the improvement of students' musical abilities after using the Auditory Intellectually Repetition (AIR) learning model with the conventional learning model. The research method used in this study is quasi-experimental which aims to determine the differences in the improvement of students' musical abilities through the application of the Auditory Intellectually Repetition (AIR) learning model with conventional learning models. The techniques used for data collection are tests, assessment rubrics and observations. The data obtained are in the form of test results and assessment rubrics as primary data and observation results as secondary data. The data analysis technique used is quantitative data analysis. The results show that the use of the Auditory Intellectually Repetition (AIR) learning model can improve the musical ability of students, this is indicated by an increase in the musicality ability of students in the experimental class using the Auditory Intellectually Repetition (AIR) learning model which is higher than the control class using conventional learning model.